① 2/(x-2)=1/(x²-4)② (x-3)/(4-3)-1=1/(x-4)

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/09 21:00:52
① 2/(x-2)=1/(x²-4)② (x-3)/(4-3)-1=1/(x-4)
x){4qF!VS645|4q=tY&`!XPMR>nPYBfP xF&Ȓx*5@ɢ(T ݭ8-3}1 b۳9ϛv>۴gMX|vӞi5<h m a8;;9;9B̟eO?ٽO6?kZ|V^.~|$?

① 2/(x-2)=1/(x²-4)② (x-3)/(4-3)-1=1/(x-4)
① 2/(x-2)=1/(x²-4)
② (x-3)/(4-3)-1=1/(x-4)

① 2/(x-2)=1/(x²-4)② (x-3)/(4-3)-1=1/(x-4)
① 2/(x-2)=1/(x²-4)
(2x+4)/(x²-4)=1/(x²-4)
(2x+3)/(x²-4)=0
2x+3=0
x=-2/3
② (x-3)/(4-3)-1=1/(x-4)
x-4=1/(x-4)
(x-4)²=1 x=5或3
有点没看懂(x-3)/(4-3)-1这个式子,化简是x-4吗?

CCBCBA
是否可以解决您的问题?